Development of Cultural Construction and Constitutional Revolution in Iran - Rabiee, Bijan; Jalalpoor, Shiva (Journal of History Culture and Art Research, 2017)
The subject of this article is the development of the cultural construction and the emergence of the Constitutional Revolution in Iran. This study, by examining the cultural structure of the Qajar era of the Naser-al-Din Shah period wants to investigate the cause of the Constitutional Revolution. The findings of this research, which have been collected by historical-analytical method, indicate that the pattern of development in the Qajar era is consistent with the pattern of unbalanced development. In this sense, by starting educational, political and military reforms in the Qajar era specially Nasser-al-Din Shah, gradually the cultural structure apart from the traditional political structure. This development provided the basis for the emergence of new intellectuals and elites with new political ideas in the field of governance methods. However, the attenuation of political structure and the backwardness of political development from cultural development faced with some obstacles. Political system instead of creating a development along with gradual cultural development and consolidating its position through the persuasion of the community, in fact to maintain integrity in the social system was resorted to force and preferred force and compulsion to persuasion. The kind of reaction and opposition of the political power structure against the modern intellectual movement, which contained new political demands in the area of governance and freedom, led to the weakness and, finally, the collapse of the Qajar political system and the constitutional revolution.